Lucio San Pedro the conservatory archetype in the midst of modernism - Guadalupe, Jocelyn Timbol (2014)
The essay presents the composer, Lucio San Pedro, as the archetype of the conservatory during the rise of the modernist movement in the Philippines. Based from interviews from former composition students and colleagues as well as archival research, an analysis of his "creative nationalist" philosophy of composition in the Philippines in comparison to the ideals of the modernist movement is discussed using socio-anthropological theories such as Bourdieu's habitus, Collins' social reproduction, as well as Ortner's practice theory. An attempt is made in positioning San Pedro as a composer in a socio-cultural light to see San Pedro's subjectivities and attached cultural meanings as results of social interactions. By looking at San Pedro as a composer in the modernist period, the theoretical framework of Bourdieu, Collins, and Ortner gives us an understanding of how San Pedro as a composer and an agent given his context and history, navigated the changing structures of music composition.
Keywords: San Pedro, Lucio Diestro, 1913-2002; Nationalism in music; Music -- Classical influences; Modernism (Music)